Seroepidemiology of Coxsackievirus A6, Coxsackievirus A16, and Enterovirus 71 Infections among Children and Adolescents in Singapore, 2008-2010 - Ang, Li Wei (PLoS One, 2015)
Coxsackieviruses A6 (CV-A6) and A16 (CV-A16) and Enterovirus 71 (EV-A71) have caused periodic epidemics of hand, foot and mouth disease (HFMD) among children in Singapore. We conducted a cross-sectional study to estimate the seroprevalence of these enteroviruses among Singapore children and adolescents. The study was conducted between August 2008 and July 2010. It involved 700 Singapore residents aged 1–17 years whose residual sera were obtained following the completion of routine biochemical investigations in two public acute-care hospitals. The levels of neutralizing antibodies (NtAb) against CV-A6, CV-A16 and EV-A71 were analyzed by the microneutralization test. The age-specific geometric mean titer (GMT) of antibodies against each of the three enteroviruses and the 95% confidence intervals (CI) were calculated. The seroprevalence of CV-A6 and CV-A16 was high at 62.7% (95% CI: 59.1–66.2%) and 60.6% (95% CI: 56.9–64.1%), respectively. However, the seroprevalence of EV-A71 was significantly lower at 29.3% (95% CI: 26.0–32.8%). About 89.7% of the children and adolescents had been infected by at least one of the three enteroviruses by 13–17 years of age. About half (52.3%) were seropositive for two or all three enteroviruses, while only 16.1% had no NtAb against any of the three enteroviruses. High NtAb levels were observed in the younger age groups. CV-A6 and CV-A16 infections are very common among Singapore children and adolescents, while EV-A71 infections are less common. Infection is continually acquired from early childhood to adolescent age.